“Detection of Helicobacter pylori in faeces of children of rural human settlements: An exploratory study in Peru“ - Moya-Salazar, Jeel (2022)
“Introduction: Helicobacter pylori is one of the major infectious agents in low-income countries, and its clinical characteristics are unknown in many populations. Children are a susceptible population and can contract these pathogens through contaminated food and water. Objectives: To determine the presence of Helicobacter pylori in children under eight years of age of rural human settlements in Peru. Methods: This exploratory study was conducted with 25 child volunteers authorized by the parents for their evaluation, without precedent of any apparent clinical manifestation. Antigen detection of H. pylori in faeces by a rapid assay onsite H. pylori Ag. Rapid test according to the manufacturer’s requirements. Has been evaluated the social determinants related to possible infection. Results: The average age (2±1.8 years) of 14 girls was different from the average age (2.7±2.2 years) of 11 boys included in the study (p=0.010). Of the total we determinate nine (36%) positive tests, which mainly affected boys (five patients 20%) under two years of age (six patients, 24%). In general, ~90% wash their hands with soap and water and ~70% wash fruits and vegetables with water before eating. In addition, >50% ate foods outside of home and ~24% was asymptomatic and did not have a specific meal schedule. Conclusions: Among rural children, Helicobacter pylori antibody was detected in 36% of the participants, unaffected by gender, and presenting specific dietary patterns.“